A Ventosa como tratamento para dor e disfunção musculoesquelética: uma revisão sistemática - Ferreira, Laura Polli (2022)
The objective of this study was to evaluate the effects of cupping therapy on pain andfunction in musculoskeletal disorders, through a systematic review. A no-time limitedsearch strategy was built with the following main terms cupping therapy , in the articles indexed in the Pubmed,Scopus and PEDro. To be included in the review, the studies had to be available asfull text, be clinical trials focusing on treatment of injuries with dry cupping therapy.The others' types of cupping are excluded. Authors used PEDro scale to assess riskof bias in the included studies and presented the results by year of sample, groups,description of the cupping technique, evaluation outcome (p value). Results. 117 studies were identified, and 11 articles were enrolled in this review.Musculoskeletal conditions found were myofascial trigger-points, low back pain, neckpain, knee osteoarthritis, female chronic pelvic pain and carpal tunnel syndrome. Drycupping showed effective in most articles (9/11); however, some articles do not havesignificant evidence of treatment compared to the control group (6/11). Conclusion. Dry cupping appears to be effective highlighting the treatment for painand function. However, the authors observed no additional effects compared toanother treatments or combined. Systematic review registration: PROSPERO number is CRD42022292635.